Initial investigation into the factors related to employment of individuals living with a spinal cord injury in a specific South African population - Michell, Lauren Anne (My University, 2015)
Many factors have been shown to play a role in employment after a spinal cord injury. Globally the rates of employment post-injury have been disappointing with a rate of 36.8% 1. METHODS This mixed methods study was divided into two phases. During phase one qualitative data was gathered. This data was used to design a questionnaire which was emailed to members of the Quadpara Association of South Africa in phase two. Bivariate data analysis was performed and a logistic regression. RESULTS Eleven themes emerged from phase one. There was a high employment rate of 79.55% at the time of the study and 92.13% had worked for remuneration since injury. There was a statistically significant association between employment at the time of the study and six factors. CONCLUSION This study had a surprisingly high employment rate post-injury. Despite few results being statistically significant there were many that are of clinical importance.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy Johannesburg, 2015
Keywords: Spinal Cord Injuries; South Africa; Employment